Maternal and Perinatal Outcome of Multiple Pregnancy in a Tertiary Care Hospital of Bangladesh - Yeasmin, Most Sabina; Uddin, Md Jalal; Khanam, Shireen Akter (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: Multiple pregnancies are prone to be associated with adverse maternal and perinatal outcome. The incidence of multiple pregnancies has shown a significant increase over the last decades. This study aimed to determine the maternal and perinatal outcome in a tertiary teaching hospital. Materials and methods: This prospective observational study was conducted in Chattogram-Maa-O-Shishu-Hospital Medical College, from July 2014 to June 2016. A total of 173 multiple pregnant women having 28 weeks completed gestation admitted for delivery were consecutively included in the study. Maternal and perinatal outcome were investigated. Results: The results show that the number of multiple pregnancies delivered during study periods was 173 with the incidence of 1.7% among total deliveries. There were 5 triplets pregnancies among these cases. The women with multiple pregnany were relatively older. There were no maternal mortality. Pregnancy complications were remarkabely higher. The main maternal adverse outcome were preterm delivery (84.97%), anaemia (39.88%), pregnancy induced hypertension (28.97%), premature rupture rupture of membrane (28.32%), postpartum haemorrhage (16.76%), antepartum haemorrhage (11.9%). The mean gestational age at delivery was 35.39 weeks for twins and 33.3 weeks for triplets. The commonest mode of delivery was by ceasarean section. The most common neonatal complications was low birth weight and most common cause of neonatal death was prematurity and neonatal sepsis. Conclusion: Majority of the multiple pregnancy is high risk one. So, all multiple pregnancies need early diagnosis, adequate antenatal, intra-natal and postpartum care to improve the outcome and should have mandatory hospital delivery. Chatt Maa Shi Hosp Med Coll J; Vol.18 (2); July 2019; Page 54-58